2021
DOI: 10.3390/toxins13040251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light on the Ochratoxigenic Fungi Aspergillus ochraceus and A. carbonarius

Abstract: Ochratoxin A (OTA) usually contaminates agricultural products such as grapes, oatmeal, coffee and spices. Light was reported as an effective strategy to control spoilage fungi and mycotoxins. This research investigated the effects of light with different wavelengths on the growth and the production of OTA in Aspergillus ochraceus and Aspergillus carbonarius. The results showed that the growth of both fungi were extremely inhibited by UV-B. Short-wavelength (blue, violet) significantly inhibited the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Greater capacity to grow than a pathogen and survival ability in harsh environments are important characteristics of biocontrol agents [43]. Many species of Aspergillus fungi can grow in environments poor in essential nutrients and thrive in a wide range of temperature (10-50 • C), pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and salinity (0-34%) conditions [44]. In the work presented here, effective antagonists against selected species of the genus Aspergillus were sought, so it was appropriate to study various aspects of the polyextremotolerance of the tested yeast strains, including their tolerance to different temperatures, pH, and salinity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater capacity to grow than a pathogen and survival ability in harsh environments are important characteristics of biocontrol agents [43]. Many species of Aspergillus fungi can grow in environments poor in essential nutrients and thrive in a wide range of temperature (10-50 • C), pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and salinity (0-34%) conditions [44]. In the work presented here, effective antagonists against selected species of the genus Aspergillus were sought, so it was appropriate to study various aspects of the polyextremotolerance of the tested yeast strains, including their tolerance to different temperatures, pH, and salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the two yeast species, only A. pullulans PP3 could grow actively under refrigerated conditions of 4 • C. This is a relevant feature of biocontrol because many fruits and vegetables are stored in such conditions. The yeast A. pullulans also showed a wider tolerance range to the medium's pH (4)(5)(6)(7)(8)(9)(10)(11) and salinity (0-12% NaCl). These properties vary depending on the strain tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of UV light with different wavelengths on the growth, production, and degradation of OTA are significant. Zhang et al [ 26 ] found that UV-B inhibited the growth of Aspergillus ochraceus and Aspergillus carbonarius , two common OTA-producing strains, at different wavelengths. Shorter wavelengths (blue and purple) significantly inhibited both OTA-producing fungi, while white light only inhibited Aspergillus ochraceus .…”
Section: Physical Methodsmentioning
confidence: 99%
“…Since OTA-producing fungi include Aspergillus and Penicillium fungi, OTA-producing fungi can contaminate both high water activity foods and low water activity foods. Water activity influences the growth and secondary metabolism of fungi, thereby regulating the production of mycotoxins [12][13][14] . There is a signalling pathway in fungi, the HOG-MAPK (high osmolarity glycerol mitogen-activated protein kinase) pathway, that can respond critically to various environmental stresses encountered by fungi, such as osmotic, oxidative, water activity, cold, heat, and light stresses [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%